Adolescent and caregiver perception of family functioning: relation to suicide ideation and attempts - Lipschitz, Jessica M. (2012)
This study assessed the relationship between perceived family functioning and two indicators of suicidality in an adolescent sample. A total of 103 adolescents psychiatrically hospitalized for suicidal ideation and/or behavior completed a battery of self-report questionnaires assessing family functioning, negative affectivity, suicidal ideation in the past week assessed by Beck’s Scale for Suicide Ideation (BSS; Beck et al., 1979), and past suicide attempts. Participants’ primary caregivers also completed a questionnaire on family functioning. A paired samples t-test evaluated overall discrepancy between adolescent- and caregiver-reported family functioning. Linear and logistic regression models were used to evaluate the simple associations between perceived family functioning and suicidal indicators (BSS and previous attempt status), as well as the associations between perceived family functioning and suicidal indicators after controlling for negative affect. Results indicated that adolescents’ ratings of family functioning were significantly worse than caregivers’ ratings, and positively associated with BSS scores and a history of suicide attempt. When negative affect was controlled for, adolescent-reported family functioning was significantly associated with BSS, but only trended toward significance with attempt status. Findings suggest that adolescents’ perceptions of family functioning may be a key contributing factor to suicidal ideation in adolescents with psychiatric disorders.